The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0034-71402004000200005
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<B>O diferencial de sal?rios formal-informal no Brasil</B>: <B>segmenta??o ou vi?s de sele??o?</B>]]>

Abstract: Sumário: 1. Introdução; 2. Metodologia e modelo econométrico; 3. Análise descritiva dos dados; 4. Resultados; 5. Conclusões e comentários finais.Palavras-chave: salários; trabalho informal; cross-section repetidas; análise de coorte.Códigos JEL: C23; J31.Neste artigo são investigados os determinantes do diferencial de salários entre os mercados de trabalho formal e informal no Brasil. Utiliza-se um método econométrico de cross-section repetidas (pseudo-paineis), no qual o agrupamento dos dados por geração, tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
11
Order By: Relevance
“…Several macroeconomic crises, with alternating periods of recession and high in ‡ation, may have also contributed to the expansion of the informal sector -the latter accounts for 87% of the jobs created between 1992 and 2002. 6 For the recent period, the Monthly Employment Survey indicates that informal employment remains high, with a share of total employment ‡uctuating between 30% and 35% over 2002-2005. Carneiro and Henley (2001) and Menezes-Filho et al (2004) show that for some workers, the informal sector may be a desirable form of employment in Brazil; they also …nd that the large informal wage gap can be explained by selection bias and consequently favor the competitive markets hypothesis. This view seems to be supported by studies on sectoral mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Several macroeconomic crises, with alternating periods of recession and high in ‡ation, may have also contributed to the expansion of the informal sector -the latter accounts for 87% of the jobs created between 1992 and 2002. 6 For the recent period, the Monthly Employment Survey indicates that informal employment remains high, with a share of total employment ‡uctuating between 30% and 35% over 2002-2005. Carneiro and Henley (2001) and Menezes-Filho et al (2004) show that for some workers, the informal sector may be a desirable form of employment in Brazil; they also …nd that the large informal wage gap can be explained by selection bias and consequently favor the competitive markets hypothesis. This view seems to be supported by studies on sectoral mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Tannuri- Pianto and Pianto (2002) and Botelho and Ponczek (2006), for instance, find evidence of the existence of wage differentials. Other authors have found the existence of wage differentials, but explain it based on non-observable characteristics of workers who joined each sector (Carneiro and Henley, 2001;Menezes-Filho et al, 2004). On the other hand, Maloney (2004) argues (based mostly on evidence from surveys) that most informal workers voluntarily choose informality because of non-pecuniary advantages (for instance, more independence in the case of self-employed workers), which could compensate for lower earnings.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, o efeito final sobre o bem-estar da economia não é positivo, porque, apesar de reduzir o custo, a informalidade implica maior instabilidade dos contratos de trabalho e perda de produtividade, resultando em um produto final menor. Menezes-Filho et al (2004) investigaram os determinantes do diferencial de salários entre os setores formal e informal do mercado de trabalho, utilizando dados da PNAD de 1981 a 2001. Os resultados revelam que os salários dos trabalhadores do setor informal são maiores do que os do setor formal e, além disso, que a escolaridade é a característica individual que mais pesa na determinação de salários entre os dois setores.…”
Section: Mudanças Institucionaisunclassified